Cancer patient preferences for the provision of information regarding emotional concerns in relation to medical procedures: A discrete choice experiment. Issue 7 (July 2020) - Turon, Heidi; Wall, Laura; Fakes, Kristy; Brown, Scott D.; Sanson-Fisher, Rob
Highlights: Providing care aligned with patient preferences is a tenet of patient-centred care. Patient preference for medical procedure information were examined. Patients preferred to receive information 1 week before the procedure. Information given face-to-face or in written materials was preferred. Abstract: Objective: To explore the preferences of people with cancer regarding the timing and format of information provision about emotional concerns that may occur when undergoing medical procedures. Methods: Eligible cancer survivors were mailed a survey containing discrete choice scenarios examining their timing and format preferences for information about potential emotional concerns associated with an upcoming hypothetical medical procedure. Results: Of 356 eligible patients, 271 (76 %) completed the survey. Both face-to-face discussion and written materials were preferred as the mode of information delivery over access to a website. In order of descending preference, participants preferred to receive the information 1 week, 3 days and the day of the procedure. There were no differences in preferences for timing or format between subgroups based on age, gender, education and cancer type. Conclusion: This study has demonstrated that cancer patients prefer receiving information about emotional concerns that might be experienced as part of a medical procedure in either written or via face-to-face format, and one week before the procedure. Practice Implications: In order to provide patient-centred care, clinicians and the healthcare system more broadly should consider patient preferences for information delivery about upcoming medical procedures. Information: preparation for medical procedures; discrete choice; oncology; patient preference; emotional response.